2017
DOI: 10.1007/s10329-017-0629-4
|View full text |Cite
|
Sign up to set email alerts
|

Mining noise affects loud call structures and emission patterns of wild black-fronted titi monkeys

Abstract: Anthropogenic noise pollution is increasing and can constrain acoustic communication in animals. Our aim was to investigate if the acoustic parameters of loud calls and their diurnal pattern in the black-fronted titi monkey (Callicebus nigrifrons) are affected by noise produced by mining activity in a fragment of Atlantic Forest in Brazil. We installed two passive acoustic monitoring devices to record sound 24 h/day, 7 days every 2 months, for a year; one unit was close to an opencast mine and the other 2.5 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…These noise levels stand above the coterminous USA range for natural sounds devoid of human influence (24-40 dB LAeq; Shannon et al, 2016) and approximate those reported at sites close to and far from an open-cast mine in Brazil (Duarte et al, 2015). In fact, the mining noise was loud enough to impact the calling patterns of black-fronted titi monkeys (Duarte et al, 2017). Correlative changes in songbird vocal activity have also been observed along a noise gradient within an urban park (Díaz, Parra & Gallardo, 2011).…”
Section: Behavioral Changes Associated With a Gradient Of Noise Levelssupporting
confidence: 59%
See 1 more Smart Citation
“…These noise levels stand above the coterminous USA range for natural sounds devoid of human influence (24-40 dB LAeq; Shannon et al, 2016) and approximate those reported at sites close to and far from an open-cast mine in Brazil (Duarte et al, 2015). In fact, the mining noise was loud enough to impact the calling patterns of black-fronted titi monkeys (Duarte et al, 2017). Correlative changes in songbird vocal activity have also been observed along a noise gradient within an urban park (Díaz, Parra & Gallardo, 2011).…”
Section: Behavioral Changes Associated With a Gradient Of Noise Levelssupporting
confidence: 59%
“…: Rangel-Negrín et al, 2009;Rimbach et al, 2013;Vanlangendonck et al, 2015;howler monkeys, Alouatta spp. : Martínez-Mota et al, 2007;Behie, Pavelka & Chapman, 2010;Rimbach et al, 2013;Vanlangendonck et al, 2015;Cantarelli et al, 2017), Pitheciidae (titi monkeys, Callicebus nigrifrons: Duarte et al, 2017) and Callithrichidae (marmosets, Callithrix penicillata: Duarte et al, 2011;Santos et al, 2017;tamarins, Saguinus leucopus: Soto-Calderón, Álvarez Cardona & García-Montoya, 2016). For example, black-tufted marmosets (C. penicillata) have been shown to avoid noisy areas of an urban park, irrespective of food availability (Duarte et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many of these threats cannot be treated independently; one or more threats may influence or occur in association with another. Moreover, some threats, for example, pathogens and microbes and viral/prioninduced diseases, may increase in severity with fragmentation (Chapman, Gillespie, & Goldberg, 2005;Goldberg et al, 2008;Young, Griffin, Wood, & Nunn, 2013); and others, for example, light pollution (Hölker, Wolter, Perkin, & Tockner, 2010) and noise pollution (Duarte, Kaizer, Young, Rodrigues, & Sousa-Lima, 2018)…”
Section: Methodsmentioning
confidence: 99%
“…Traffic noise reduced foraging efficiency in most bats [94]. Monkeys also live in noise free areas as exhibited by a study in which continuous noise was supplied in the habitat of the monkeys in Brazil, monkeys moved from that area to noise free area indicating that they also do not like noise [95]. Noise effects on wildlife have also been widely studied and results indicated that they also prefer to live away from noise like bears, wolves, ants, lions and larger animals like elephants and whales [96] ( Table 2).…”
Section: References Effects Referencesmentioning
confidence: 98%